Pragmatic Strategies in the Translation of Surah Al-Baqarah (Ayahs 2-30) by Mufti Taqi Usmani: A Skopos Theory Analysis - Muhammad Ali Shahid; Mamoona Hassan; Muhammad Imran (International Research Journal of Arabic and Islamic Studies, 2024)
Translating is not the same thing as transferring knowledge. The translators use adaptations in translation to retain the original meaning of the source text. These adaptations help a translator to make an original text for the target reader. In this thesis, the researcher aimed to find the implications of pragmatic adaptations on the English Translation of Surah Al-Bakrah (Ayah 2-30) by Mufti Taqi Usmani. The researcher has selected Skopos theory in which Garant (2008) model of pragmatic adaptations is used as a method that focuses on the analysis of the translated text. The purpose of the English translation of the Quran is to make its teachings and guidance accessible to English-speaking individuals who do not understand Arabic, the language in which the Quran was originally revealed. English translations of the Quran provide an opportunity for people who do not speak Arabic to study and reflect upon the Quran's message of guidance, wisdom, and moral values. English translations of the Quran have played a significant role in spreading Islam and facilitating the growth of Muslim communities in English-speaking countries. It has allowed for a greater understanding of the Quran's message which will provide a straight path the Muslims to live a guided and principled life. This study will be useful in guiding in understanding the pragmatic adaptations during the translation process. This study assists the readers and translators to comprehend the original text and change its meaning in the translated text. Teachers of translation studies, scholars, and keen readers can benefit from this study.